Cognitive impairment in heart failure patients: association with abnormal circadian blood pressure rhythm: a review from the HOPE Asia Network - Komori, Takahiro; Hoshide, Satoshi; Turana, Yuda; Sogunuru, Guru Prasad; Kario, Kazuomi; Wang, Ji Guan; Chia, Yook Chin * (Sprinter Nature, 2023)
Cognitive impairment (CI) is frequently a comorbid condition in heart failure (HF) patients, and is associated with increased cardiovascular events and death. Numerous factors contribute to CI in HF patients. Decreased cerebral blood flow, inflammation, and activation of neurohumoral factors are all thought to be factors that exacerbate CI. Hypoperfusion of the brain due to decreased systemic blood flow, cerebral venous congestion, and atherosclerosis are the main mechanism of CI in HF patients. Abnormal circadian BP rhythm is one of the other conditions associated with CI. The conditions in which BP does not decrease sufficiently or increases during the night are called non-dipper or riser BP patterns. Abnormal circadian BP rhythm worsens CI in HF patients through cerebral congestion during sleep and atherosclerosis due to pressure overload. Interventions for CI in HF patients include treatment for HF itself using cardiovascular drugs, and treatment for fluid retention, one of the causes of abnormal circadian rhythms.